Macrophage Bridging Conduit Trafficking of HIV-1 Through the Endoplasmic Reticulum and Golgi Network - Kadiu, Irena (American Chemical Society, 2011)
[Image: see text] Bridging conduits (BC) are tubular protrusions that facilitate cytoplasm and membrane exchanges between tethered cells. We now report that the human immunodeficiency virus type I (HIV-1) exploits these conduits to accelerate its spread and to shield it from immune surveillance. Endosome transport through BC drives HIV-1 intercellular transfers. How this occurs was studied in human monocyte-derived macrophages using proteomic, biochemical, and imaging techniques. Endosome, endoplasmic reticulum (ER), Golgi markers, and HIV-1 proteins were identified by proteomic assays in isolated conduits. Both the ER and Golgi showed elongated and tubular morphologies that extended into the conduits of polarized macrophages. Env and Gag antigen and fluorescent HIV-1 tracking demonstrated that these viral constituents were sequestered into endocytic and ER-Golgi organelles. Sequestered infectious viral components targeted the Golgi and ER by retrograde transport from early and Rab9 late endosomes. Disruption of the ER-Golgi network impaired HIV-1 trafficking in the conduit endosomes. This study provides, for the first time, mechanisms for how BC Golgi and ER direct cell–cell viral transfer.